Ф.М. Достоевский: Юмор, парадоксальность, демонтаж - Farafonova, Daria; Salmon, Laura; ALOE, Stefano (Biblioteca di Studi Slavistici, 2023)
While the analysis of humor, paradox, and deliberate deconstruction has generally occupied a marginal position in the study of Dostoevsky's universe, it seems impossible to understand his poetics without pointed attention to these categories. The present book aims to fill the existing gap by focusing on the nature of ambivalent humor, paradoxicality, and methods of 'de-automatizing' consciousness through deconstruction, arguing that these are central elements in Dostoevsky's creative arsenal. It is precisely the dialogical and paradoxical nature of his artistic method that enables such different and sometimes contradictory readings. Dostoevsky, who proclaimed «the excitement of compassion» as the secret of humor (in the 'funny' there is always sadness and even despair), more generally exposes in his writing the structural duality of all phenomena.